Corrective Justice For Medical Personnel Who Violate The Law: Where Is The Professional Organizations Involvement? - Sudarta, Gede Dicky Wahyu Putra; Darma, I Made Wirya; Chansrakaeo, Ruetaitip (Faculty of Law, Universitas Jenderal Soedirman, 2023)
The provision of criminal sanctions for medical personnel who violate the law in the form of gross negligence creates legal uncertainty apart from the unclear definition of serious negligence and does not involve the role of professional medical professional organizations in determining criminal witnesses for medical personnel. This study aims to formulate aspects of corrective justice for medical personnel who violate the law, especially in the realm of criminal law. This research is a normative legal research with a concept and statutory approach. The results of the study confirm that the criminal responsibility of medical personnel requires the role of the professional organization of the medical personnel concerned. This is because the assessment of the professional organization of medical personnel is important as a form of guaranteeing justice and legal certainty for medical personnel. Corrective justice-based medical personnel accountability orientation can actually be carried out by involving the roles and recommendations of medical professional organizations. In addition, health law reform is also needed by formulating criminal sanctions for medical personnel based on ultimum remidium, namely utilizing non-prison criminal sanctions in order to achieve justice for medical personnel